Aplicación de politicas de comunicación para protección de los derechos laborales de los trabajadores, empresas de transporte público urbano de Trujillo, año 2016 - Sanchez Chavez, Silver Yordin (2017)
This paper entitled “Application Communication Policy For The Protection Of Workers Labor Rights, Urban public transport companies of Trujillo, Year 2016”. General objective, determining that lack communication policies implemented to protection of labor rights of workers, recognize and apply towards improvement. This research is descriptive, not experimental design. Data collection was performed, a database that provided various companies in the transport sector; questionnaire guide Analysis: survey also techniques, content analysis (gather data files) and instruments as used. Which reflected the problems we currently are. The results revealed that the implementation of communication policies towards the protection of laborados rights influence positively, since workers in the same transport companies can develop not only economically but comprehensive and securely in their work as collectors and drivers, allowing their full potential, reaching change their lives and those of their families.